2016
DOI: 10.1007/s00784-016-1816-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of IL-1β, IL-1ra, and IL-10 levels and outcome of periodontal therapy in chronic periodontitis with familial Mediterranean fever

Abstract: Following treatment, GCF IL-1β and GCF IL-1ra levels were decreased in FMF-CP group. GCF IL-10 levels were increased in FMF-CP group compared to other groups. Also, the serum cytokine levels associated with periodontal inflammation in FMF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 48 publications
4
13
1
Order By: Relevance
“…Only four studies to date have introduced clinical periodontal parameters to analyze patients with FMF without amyloidosis. [37][38][39][40] Although our results are similar to those studies that display increased gingival index values in patients with FMF without amyloidosis, 38,39 it has also been reported that patients with FMF have significantly lower PD and CAL values than those of the control group. 38 In another study, the same investigators showed that patients with FMF and chronic periodontitis display reduced oxidative stress and increased antioxidant status compared with those in the systemically healthy control group.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Only four studies to date have introduced clinical periodontal parameters to analyze patients with FMF without amyloidosis. [37][38][39][40] Although our results are similar to those studies that display increased gingival index values in patients with FMF without amyloidosis, 38,39 it has also been reported that patients with FMF have significantly lower PD and CAL values than those of the control group. 38 In another study, the same investigators showed that patients with FMF and chronic periodontitis display reduced oxidative stress and increased antioxidant status compared with those in the systemically healthy control group.…”
Section: Discussionsupporting
confidence: 90%
“…According to our results, patients with FMF had stronger clinical periodontal parameters than those of systemically healthy controls. Only four studies to date have introduced clinical periodontal parameters to analyze patients with FMF without amyloidosis . Although our results are similar to those studies that display increased gingival index values in patients with FMF without amyloidosis, it has also been reported that patients with FMF have significantly lower PD and CAL values than those of the control group .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, FMF patients had higher levels of clinical periodontal parameters (PD and CAL) than the control group. Although our results are similar to those of few clinical studies in FMF patients with no amyloidosis, Bostancı et al . have stated decreased clinical periodontal parameters in the FMF group.…”
Section: Discussionsupporting
confidence: 91%
“…have stated decreased clinical periodontal parameters in the FMF group. There are marked methodological differences between the current study and Bostancı and colleagues’ studies . In those studies, patients with FMF were diagnosed according to the Tell‐Hashomer criteria without genetic analysis, which is different from our study.…”
Section: Discussioncontrasting
confidence: 65%